Percentages of serum, liver and adipose tissue fatty acids and body weight are affected in female rats by long-term Central kisspeptin treatments - Sahin, Zafer; Ozcan, Mete; Ozkaya, Ahmet; Canpolat, Sinan; Kutlu, Selim; Kelestimur, Haluk (Taylor & Francis Ltd, 2023)
This study was conducted to determine the possible effects of long-term exogenous kisspeptin and its antagonist P234 on serum, liver and adipose tissue fatty acids (FA) profiles, as well as body weight, in female rats. Kisspeptin (50 pmol) and P234 (1 nmol) were administrated to the weaned Sprague-Dawley female rats by an intracerebroventricular injection from the 26th postnatal day to the 60th postnatal day. Percentages of the serum total saturated FA ( n-ary sumation SFA) and total monounsaturated FA ( n-ary sumation MUFA) were lower in the kisspeptin group. In the adipose tissue, n-ary sumation SFA was lower and total unsaturated FA higher in the P234 group. Moreover, long-term central kisspeptin injection caused a decrease in the body weight. When compared to the kisspeptin group, the final body weights were higher in the P234 and kisspeptin + P234 groups. According to our results, we suggest that kisspeptin has a regulatory role in FA metabolism and regulation of body weight.
Keywords: Kisspeptin; kisspeptin antagonist; fatty acids; body weight; energy metabolism; rat